The IRX–β dust attenuation relation in cosmological galaxy formation simulations. Issue 2 (6th November 2017) - Narayanan, Desika; Davé, Romeel; Johnson, Benjamin D.; Thompson, Robert; Conroy, Charlie; Geach, James
Abstract: We utilize a series of galaxy formation simulations to investigate the relationship between the ultraviolet (UV) slope, β, and the infrared excess (IRX) in the spectral energy distributions (SEDs) of galaxies. Our main goals are to understand the origin of and scatter in the IRX–β relation; to assess the efficacy of simplified stellar population synthesis screen models in capturing the essential physics in the IRX–β relation; and to understand systematic deviations from the canonical local IRX–β relations in particular populations of high-redshift galaxies. Our main results follow. Young galaxies with relatively cospatial UV and IR emitting regions and a Milky Way-like extinction curve fall on or near the standard Meurer relation. This behaviour is well captured by simplified screen models. Scatter in the IRX–β relation is dominated by three major effects: (i) older stellar populations drive galaxies below the relations defined for local starbursts due to a reddening of their intrinsic UV SEDs; (ii) complex geometries in high- z heavily star-forming galaxies drive galaxies towards blue UV slopes owing to optically thin UV sightlines; (iii) shallow extinction curves drive galaxies downwards in the IRX–β plane due to lowered near-ultraviolet/far-ultraviolet extinction ratios. We use these features of the UV slopes of galaxies to derive a fitting relation that reasonably collapses the scatter back towards the canonical local relation. Finally, we use these results to develop an understanding for the location of two particularly enigmatic populations of galaxies in the IRX–β plane: z  ∼ 2–4 dusty star-forming galaxies and z  > 5 star-forming galaxies.